FUNGSI KARANG TARUNA DALAM PENYELENGGARAAN PEMERINTAH DESA MAUKELI KECAMATAN MAUPONGGO KABUPATEN NAGEKEO - Gabriel Nasarius Laben Tukan; Veronika Ruba Pena; Maximianus Ardon Bidi; Eusabius Sepa Rera Niron (Journal Education and Government Wiyata, 2026)
This community service activity was carried out with the aim of increasing the knowledge and active involvement of Karang Taruna members in the administration of government in Maukeli Village, Mauponggo District, Nagekeo Regency. One of the problems faced is the low participation of youth in village government affairs, which is caused by a low understanding of the functions and important roles of Karang Taruna. For this reason, this service was carried out through various methods such as socialization, group discussions, and short training involving village officials, community leaders, and Karang Taruna members. The material presented included the role of Karang Taruna in village development, involvement in planning and implementing village programs, and strengthening the capacity of youth organizations. The results of this activity showed an increase in knowledge and enthusiasm of youth in supporting village programs, as well as a joint commitment to improve cooperation between Karang Taruna and the village government in a sustainable manner. It is hoped that through this socialization, Karang Taruna can function effectively as a strategic partner for the village government in creating participatory, inclusive, and sustainable development.